Macroinvertebrados de suelo en plantaciones de Cedrelinga catenaeformis (ducke) ducke “tornillo” y bosque secundario de tierra firme durante periodo menos lluvioso, Puerto Almendra-Loreto - Funes Tecco, Louis (2025)
A study was conducted to know the composition of soil macroinvertebrates during the least rainy period, in 02 areas with 3 replicates each, belonging to plantions of Cedrelinga Catenaeformis “tornillo” and secondary mainland forest in the Center for Research and Forestry Education (CIEFOR) – Almond Port macroinvertebrates , we worked with the methodology by the International Tropical Soil Biology and Fertility Program (TSBF), was used and 15 monoliths were placed randomly on the ground in each area. The richness recorded 35 taxonomic groups, 02 phyla, 07 classes, 18 orders and 24 families, the most diverse class was Insecta and the orden with the highest number of families was Coleóptera. The total density was 1971 ind/m2, althougth the secondary mainland forest system recorded the a lot of individuals, no significant differences are evident between the study areas. The groups are with the highest density belong to Haplotaxiada, Isotomidae, Termitidae, Sthaphylinidae and Formicidae. The highest biomass was recorded in plantions of Cedrelinga catenaeformis “tornillo” influenced by the group Haplotaxiada with 45.8 gr/m2. Detritivores are reported as the functional group with the highest density. 504 ind/m2 in secondary land forest system and 403 ind/m2 in Cedrelinga catenaeformis “tornillo” planting system. In conclusion the composition of soil macroinvertebrates in the plantations of Cedrelinga catenaeformis “tornillo” and secondary forest of on here had and medium richness with densities and biomass greater than 1000 ind/m2 and 30 gr/m2, various functional groups during the rainy a little month season.